Unraveling the mechanisms of fruit abscission in Morus laevigata through multi-omics approaches - Yang, Jiahu; Li, Sha; Li, Zhennan; Xuan, Yahui; He, Jiamei; Ruan, Mingju; Feng, Yuming; Tao, Zhenyang; Kang, Xiaoru; Li, Zhengang (Frontiers in Plant Science, 2025)
IntroductionMorus laevigata (long-fruited mulberry) is rich in active components and possesses significant nutritive value. The fruitlet stage represents a critical period for fruit abscission, and elucidating the underlying biological mechanisms of this process can provide a theoretical foundation for breeding more stable and abscission resistant cultivars.MethodsFruit peduncles at the fruit set stage (April to May) were selected as experimental materials, including both abscising and non-abscising fruits. Morphological analysis of the peduncle abscission zone was conducted to examine structural differences. Additionally, transcriptomic and metabolomic analyses were performed to investigate gene expression and metabolite changes associated with fruit abscission.ResultsMorphological analysis of the peduncle abscission zone in abscising fruits revealed enlarged intercellular spaces and disorganized cell arrangements. Transcriptomic and metabolomic analyses indicated that genes and metabolites related to fruit abscission were primarily involved in plant hormone signal transduction, and starch and sucrose metabolism pathways. Auxin and abscisic acid were identified as key regulators, modulating the expression of cell wall-degrading enzymes, which facilitated cell wall loosening and degradation, ultimately leading to fruit abscission. Furthermore, alterations in energy metabolism were found to play a pivotal role in this process.ConclusionThese findings contribute to a deeper understanding of the physiological mechanisms underlying fruit development and abscission, offering valuable insights into mulberry breeding and the sustainable advancement of modern agriculture.